The effects of common yarrow (Achillea millefolium Linnaeus), cinnamon (Cinnamomum zeylanicum Blume) and rosemary (Rosemarinus officinalis Linnaeus) hydrosols on the some immunological and hematological parameters of common carp (Cyprinus carpio L., 1758) - Altinterim, Basar; Danabas, Durali; Aksu, Onder (Cellular and Molecular Biology, 2018)
In this study, the effects of some plant hydrosols (distilled plant waters) based upon some hematological parameters and Nitroblue Tetrazolium (NBT) activities in the common carp (Cyprinus carpio Linnaeus, 1758) infected with Yersinia ruckeri were investigated. In the trial, it was utilized totally 200 common carps with 54.3±6.7 g mean live weight and 15.7±1.8 cm mean total lenght. The 10% rate of the common yarrow (Achillea millefolium Linnaeus) hydrosol; 0.5% rate of the cinnamon (Cinnamomum zeylanicum Blume) hydrosol; and 5% rate of the rosemary (Rosemarinus officinalis Linnaeus) hydrosol were applied to fish as a bath treatment. The erythrocyte (RBC), leukocyte count (WBC), hematocrit value (HCT), haemoglobin amount (Hg), mean corpuscular volume (MCV), mean corpuscular haemoglobin (MCH), mean corpuscular haemoglobin concentration (MCHC), and activities of NBT in the blood samples taken from the caudal vena of the control and experimental fish groups were analyzed in the 7th, 14th, and 21st days of the exposure treatment. At the end of the research, HCT, Hg, RBC, WBC, MCH and MCV values decreased in the C-2 Group (the control group contain pathogen) compared to the C-1 Group (the control group no contain pathogen), except MCHC value. The NBT activities in the C-1 Groups increased at the 14th day, but decreased quite a few at the 21st day. It has been consequently reached the conclusion that the bath treatments of the some plant hydrosols might be beneficial in increasing of antibacterial properties and in strengthening of defense mechanisms of common carp against Y. ruckeri pathogen.